2017
DOI: 10.1136/bmjopen-2016-014894
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between job satisfaction, work stress, work–family conflict, and turnover intention among physicians in Guangdong, China: a cross-sectional study

Abstract: ObjectiveTo investigate the relationship between job satisfaction, work stress, work–family conflict and turnover intention, and explore factors associated with turnover intention, among physicians in Guangdong Province, China.MethodsFrom August to October 2013, physicians completed questionnaires and scales with regard to their job satisfaction, work stress, work–family conflict, and turnover intention. Binary logistic regression and structural equation modelling (SEM) were used in data analysis.ResultsA tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
197
2
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(266 citation statements)
references
References 68 publications
(58 reference statements)
29
197
2
14
Order By: Relevance
“…These results support previous empirical findings that work–family conflict has a stronger effect on job satisfaction than does family–work conflict (Kossek & Ozeki, ) and that both work–family conflict and family–work conflict are bi‐directional and yet different constructs with unique antecedents (Byron, ; Michel, Kotrba, Mitchelson, Clark, & Baltes, ). Our finding regarding the indirect effect of work–family conflict on turnover intention through job satisfaction is also in line with previous research (Lu et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…These results support previous empirical findings that work–family conflict has a stronger effect on job satisfaction than does family–work conflict (Kossek & Ozeki, ) and that both work–family conflict and family–work conflict are bi‐directional and yet different constructs with unique antecedents (Byron, ; Michel, Kotrba, Mitchelson, Clark, & Baltes, ). Our finding regarding the indirect effect of work–family conflict on turnover intention through job satisfaction is also in line with previous research (Lu et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Similar to previous studies, the results of our study indicated that GPs with fewer professional development opportunities experienced higher turnover intention. Fewer career development opportunities seemed to drive GPs away from primary care.…”
Section: Discussionsupporting
confidence: 91%
“…Fewer career development opportunities seemed to drive GPs away from primary care. One possible explanation was that few professional development opportunities could reduce their work efficiency, cut job enthusiasm, or even result in turnover . Thus, providing more development opportunities could help attract more GPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work-family conflict was understood as having consequences on an employee's satisfaction with their work -their satisfaction with their job and the organization, and on an employee's affective commitment -their willingness and enthusiasm to support the organization (Lu et al, 2017;Nohe, Meier, Sonntag, & Michel, 2015). Dissatisfaction and disengagement activates the process of employee withdrawal, manifesting as turnover intention and culminating in the decision to leave.…”
Section: Discussionmentioning
confidence: 99%